2020
DOI: 10.1371/journal.pntd.0007719
|View full text |Cite
|
Sign up to set email alerts
|

Responses of the putative trachoma vector, Musca sorbens, to volatile semiochemicals from human faeces

Abstract: The putative vector of trachoma, Musca sorbens, prefers to lay its eggs on human faeces on the ground. This study sought to determine whether M. sorbens females were attracted to volatile odours from human faeces in preference to odours from the faeces of other animals, and to determine whether specific volatile semiochemicals mediate selection of the faeces. Traps baited with the faeces of humans and local domestic animals were used to catch flies at two trachoma-endemic locations in The Gambia and one in Eth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…). The Musca domestica was also the most captured fly in three different regions of Africa in a previous study 16 . However, the transmission of trachoma in Africa is related to M. sorbens, and the presence of C. trachomatis has been demonstrated only in this species 2 , 16 - 18 .…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…). The Musca domestica was also the most captured fly in three different regions of Africa in a previous study 16 . However, the transmission of trachoma in Africa is related to M. sorbens, and the presence of C. trachomatis has been demonstrated only in this species 2 , 16 - 18 .…”
Section: Discussionmentioning
confidence: 68%
“…The Musca domestica was also the most captured fly in three different regions of Africa in a previous study 16 . However, the transmission of trachoma in Africa is related to M. sorbens, and the presence of C. trachomatis has been demonstrated only in this species 2 , 16 - 18 . Generally, the female of M. sorbens is associated with the transmission of trachoma, proliferating in human feces exposed in the environment 4 , 16 .…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The end goal of this campaign is to provide access to sanitation, including lavatories with soap, to all Nigerians, especially in rural areas. Studies have shown that access to basic pit latrines lead to a significant reduction in the numbers of eye-seeking flies, correlating with an overall reduction in trachoma [29,30].…”
Section: Environmental Factorsmentioning
confidence: 99%